The Effort of Junior High English Teachers in Improving Storytelling Skills - Sukma Nur Ardini (Universitas PGRI Semarang, 2019)
This study aims at determining the extent of junior high English teachers’ effort in improving the ability in coaching storytelling as well as identifying the constraints faced by them and their attempts to solve these problems. This research is mixed method) is descriptive qualitative and quantitative research. Throughout the public and private junior high school in Central Java is the population, while a sample of 10 teachers and 20 students obtained using purposive sampling of 10 junior high school in Central Java. Observation, interviews, questionnaires, and documentation used to collect data. The results showed that the coaching efforts have achieved good category. However, it should be improved in some perspective; from the perspective of professionalism and the support of sponsors. Constraints faced is a narrow time, exercise without support or without sponsorship funds, the ability of students who are not primarily the ability of pronunciation that still needs a lot of improvement, and teacher resources that do not meet or schools that do not support the maximum. It is undeniable that the efforts of teachers / coaches in this case is very important, then the City and Provincial Education Department should give special attention to the teachers so that they increase the English proficiency.